The Implemantation of Media Studies Based on 3D Visualization and Animation in Distance Learning Toward the Result Study of High School in Topic of Chemical Bonds - Efrizal Siregar (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
The impact of covid-19 makes the teaching and learning process of students not direct. The learning process takes place online or PJJ. However, this shift in learning styles affects the learning outcomes obtained by most students. For this reason, the researcher wants to conduct a study to determine the increase in student learning outcomes on the subject of Chemical Bonds by using 3D visualization and animation based learning media in distance learning. The population of this study were students of class X at SMA Panca Budi which consisted of 6 classes. Each class consists of 32 to 35 students. The sample selection technique was purposive sampling. The selected sample is class X MIA-5 as an experimental class which is treated using 3D-based media and animation. While class X MIA-6 as a control class that uses conventional treatment, namely PJJ with lecture and question and answer methods. This study uses a test instrument and no test that has been tested and has been valid. Firstly, the data on student learning outcomes were tested for normality and homogeneity, where the results obtained by the two sample groups were homogeneous and normally distributed. Hypothesis testing is carried out using quasi experiment anova, namely the right side with the results of this study at a significance level of 5% (α = 0.04) indicating that F hit (F=54.021, P=0,000) then Ho is rejected. Thus, it shows that there is an effect of learning media based on 3D visualization and animation on PJJ on learning outcomes. Correlation test was conducted to determine the relationship between student activities and student learning outcomes. The results showed that Fhit  ( F=19,645, P=0,000) then HO  was rejected. Thus, there is a significant correlation between student activities with 3D-based learning media and animation with student learning outcomes of 45.4%.